2016
DOI: 10.1109/tia.2015.2469778
|View full text |Cite
|
Sign up to set email alerts
|

Flux-Weakening Control of Switched Reluctance Machines in Rotating Reference Frame

Abstract: A flux weakening control for switched reluctance motors (SRM) in the rotating reference frame is proposed in this paper. This rotating reference frame control of SRM mimics the control of synchronous machines (SM). The method uses the periodic nature of the quasi-sinusoidal static torque characteristics to establish the rotating reference frame. A novel negativity removal and simplified non-linearity handling block is introduced to ensure a smooth torque sharing among different phases and adjust for the SRMs u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, iterative calculation is required in the reference current generation for the saturated SRM. In [127], [128], the authors directly map a synchronous reluctance machine to the SRM, by maintaining equal torque. From the perspective of control variables, the SRM is controlled in a vector torque control like method.…”
Section: ) Vector Controlmentioning
confidence: 99%
“…However, iterative calculation is required in the reference current generation for the saturated SRM. In [127], [128], the authors directly map a synchronous reluctance machine to the SRM, by maintaining equal torque. From the perspective of control variables, the SRM is controlled in a vector torque control like method.…”
Section: ) Vector Controlmentioning
confidence: 99%
“…In [24], an adaptive flux‐weakening control method being suitable for the wide speed range of SRM is proposed under the d–q rotating reference coordinate. A flux‐weakening control method for SRM under the rotating reference coordinate is proposed [25], which offers the smooth torque at the low‐speed operation of SRM. Unfortunately, the flux‐weakening control method for SRM increases the complexity of calculation and the difficulty of implementation due to the introduction of the d–q rotating reference coordinate.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, parameters that affect the performance measures such as turn-on/off angles (commutation), current regulation, DC bus voltage adjustments should be treated properly [5,6]. During the last decades, numerous research has been reported on converter topologies and control methods for improving the performance and operating range, as well as the torque ripple and acoustic noise reduction [2,7,8]. Among many SRM converter structures, asymmetricbridge converter topology is considered as the traditional SRM drive.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nonlinear magnetic characteristics of the SRM, it is a challenge to conduct an accurate current regulation. Simple average PI control [14], hysteresis control, DQ control [7], [25], sliding mode control [26], back emf predictive control [27] are some of these structures.…”
Section: Introductionmentioning
confidence: 99%